PENGARUH PENGGUNAAN KOMPRES HANGAT DALAM PENGURANGAN NYERI PERSALINAN KALA I FASE AKTIF DI RSUD CUT NYAK DHIEN MEULABOH KABUPATEN ACEH BARAT TAHUN 2025 - Rica Muriasih; Anita Anita; Irnawati Irnawati; Rina Julianti; Nurdahliana Nurdahliana (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
This study aims to determine the effect of warm compress application on labor pain intensity during the active phase of the first stage of labor at Cut Nyak Dhien Regional Public Hospital, Meulaboh. This research used a quasi-experimental design with a one group pre-test and post-test approach. The population consisted of all laboring mothers at the hospital from January to December 2024 (762 individuals). Samples were selected using purposive sampling, totaling 88 respondents. The results showed that before the intervention, 83% of respondents experienced severe pain. After the warm compress was applied, there was a significant decrease in pain with an average reduction score of 0.557 (p < 0.001). A total of 55.7% of respondents reported reduced pain, while 44.3% experienced no change. Pain distribution shifted from primarily severe (83%) to severe (44.3%), moderate (38.6%), and mild (17%). Warm compresses are effective in reducing the intensity of labor pain during the active phase of the first stage, although the effects may vary among individuals. Warm compresses can be considered as a standard non-pharmacological intervention in maternity care to help manage labor pain effectively.